Investigation of the Electric Field of the Plane Capacitor Round Hole - Bansevicius, R.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2004)
The round hole of the plain capacitor, filled by electrorheological fluid ERF can be applied for construction of the valves controllingby electric field. It is important to know distribution of electric field in the hole, when the difference between the plates of capacitor iscreated. The electric field of hole was investigated using finite element method. The two- and three-dimensional models were used. Themodelling results confirm analytical expressions obtained previously for calculation of electric field strength on the axis of hole and inany point of hole. The capacitive circuit was presented for evaluation of influence of permittivities of dielectric between the plates andERF to the strength of electric field in the hole. The dielectric material between the plates of capacitor fractionally amplifies the field ofhole. But the field of hole decreases with increment of ERF permittivity. The dependences of electric field strength on the distance ataxis in several layers of hole are presented. The approximated expressions are obtained for calculation of value and direction of electricfield strength in any point of hole, if relative permittivity of ERF is in interval 1-7. The field of hole of multilayer capacitor withopposite fields was investigated. The field in any layer of such capacitor is lesser than in analogical monolayer capacitor. The field inone layer of multilayer capacitor can be amplified in comparison with monolayer capacitor, if the difference of potentials is connectedto alone layer only. (Ill. 8, bibl. 1; in Lithuanian; summaries in Lithuanian, English, Russian).